The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.4018/978-1-4666-8699-1.ch018
|View full text |Cite
|
Sign up to set email alerts
|

Giving Brand Image to a Nation

Abstract: Adapting Keller's brand image theory (1993), this paper presents an exploratory framework for giving brand image to a nation. Utilizing unstructured interviews, the result suggests that tourism and hospitality attributes can be used for giving brand image to a nation and behavioral intention. Specifically, the result denotes that the perceived brand image of a nation is formed according to tourists' cognitive and affective beliefs, which at the end; influence the action to recommend to others and/or for repeat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 47 publications
0
3
0
Order By: Relevance
“…Using historical averages, the Google Maps API generates credible predictions that take into account traffic conditions and congestion losses through real-time location data [18]. Given the strong correlation between the time cost and distance, only the time cost was retained, with the average speed derived for further analysis.…”
Section: Analysis Of Tourist Accessibilitymentioning
confidence: 99%
See 2 more Smart Citations
“…Using historical averages, the Google Maps API generates credible predictions that take into account traffic conditions and congestion losses through real-time location data [18]. Given the strong correlation between the time cost and distance, only the time cost was retained, with the average speed derived for further analysis.…”
Section: Analysis Of Tourist Accessibilitymentioning
confidence: 99%
“…This analysis revealed that tourists expressed attention, importance, and interest in what sensitised or satisfied them during their visits to these attractions (Figure 2). Using historical averages, the Google Maps API generates credible predictions that take into account traffic conditions and congestion losses through real-time location data [18]. Given the strong correlation between the time cost and distance, only the time cost was retained, with the average speed derived for further analysis.…”
Section: Analysis Of Tourist Satisfaction Based On Interviewsmentioning
confidence: 99%
See 1 more Smart Citation